Trends that will Affect Technology and Resource Decision in Academic Libraries in Near Future - Upadhyay, Dr Navin; Upadhyay, Navin (IEEE, 2015)
In the last twenty years, Information Communication Technology (ICT) has witnessed rapid growth and change on very low interval. This change has affected the scholarly communication and higher education system globally. The changing information seeking behavior and recent trends in ICT has forced library professionals worldwide to rethink on the traditional way of purchasing resources and technology in academic libraries. Now librarians have to think and watch carefully the trends in higher education, ICT, Information seeking behavior of users and the social media, so that they may take judicious and economical decision in the front of resources and technology which is the most vital part of the library system.
Keywords: Academic library; cloud computing; scholarly communication; online resources